Shear strength of soil by using rice husk ash waste for sustainable ground improvement - Abdelmageed Atef Abdelmageed Shehata; Alex Otieno Owino; Md. Yachin Islam; Zakaria Hossain (Discover Sustainability, 2024)
Abstract In the global construction industry, areas characterized by weak and expansive soils are on the rise, necessitating effective solutions for strength enhancement. Addressing this concern, sustainable soil amendments have gained attention, with rice husk ash (RHA) from rice milling industries being a notable focus. Our experimental study aimed to assess the shear strength of this innovative construction material, introducing a unique approach that considers subgrade layers with minimal cement dosage, including upper, bottom, and double layers a novel contribution yet unexplored in existing literature. In addition to conventional mechanical testing, we employed SEM (Scanning Electron Microscopy) and EDS (Energy-Dispersive X-ray Spectroscopy) analyses to comprehensively explore the treated soils' microstructural and elemental composition aspects. Examining sixteen specimen combinations of weak expansive soil-RHA-cement, varying proportions of RHA (2%, 4%, 6%) and cement (2%, 4%, 6%) were mixed to understand their effects on shear strength parameters. Our findings revealed significant shear strength improvement in each subgrade layer, with specimen 6%RHA6%C in the lower subgrade layer exhibiting the highest cohesive strength at 143 kN/m2. Notably, the double layer configuration, specimen 2%RHA6%C, achieved maximum deviatoric stresses of 383 kN/m2. This novel construction material contributes to effective waste management and presents an innovative engineering solution for sustainable ground improvement, offering promising prospects for future geotechnical advancements.